E-modul: Alternatif Media Pembelajaran Online Untuk Perkuliahan Sistem Informasi Manajemen - Rino Rino; Zul Afdal; Armida S Armida S; Adman Adman; Abdul Latif; Riska Khairunnisa; Meizi Syafri Yendi (Jurnal Inovasi Pendidikan Ekonomi (JIPE), 2022)
This study aimed to develop the E-module, which is a a Google Sites–based online module to increase students' achievement in bachelor program degree economic education. It would be able to facilitate lecture’s carrying out learning in an effective and efficient manner, especially when distance learning is implemented. This research and development study had five stages: analysis, design, development, Implementation and evaluate. The e-module quality is validated using expert judgment, and its applicability to students is then evaluated. The research subjects are students in of class management information system class. The results reveal that the E-module had high quality in the appearance and programming aspects based on expert judgment. Then, based on the practicality test, students and lecture's determined that the E-module was very practical to use because it was visually appealing, the menus and pane navigation functioned well, and the content was appropriate for students. There is a significant (significant) difference between the average learning outcomes of the experimental class and the control class. As a result, it can be concluded that the E-module has high quality, practice, and would be widely used by lecture’s in conducting classroom learning.